Intelligent Railway Safety Detection Device At Railway Platform - Sunitha V. Doraisamy; Izwah Ismail (Jurnal Kejuruteraan, Teknologi and Sains Sosial (JKTSS), 2024)
Railway stations are often linked with accidents and have safety issues at the track or platform edge. The number of passengers usually rises during the peak hours which causes the railway platform to be packed and crowded. People with disabilities who use commuter as their basic mode of transport are also at risk for accidents at the platform edge. To prevent any accidents or hazards from happening, an improvement method was identified to improvise the safety at the railway platform. The objective of this study is to develop a detection device which is able to alert passengers at the platform edge of the railway station. Once the prototype of the intended device was developed, it is further validated with experts. The study has led to the development of a railway safety detection device which uses a type of sensor called ultrasonic sensor. The instruments used to develop the sensor are Arduino UNO R3, male to male dupont cable, buzzer, LED light, USB cable, breadboard, 220K ohm resistor and battery connector. The end result shows that the desired objectives for this study has been achieved. The development of this railway safety detection device contributes towards the safety at the platform edge of the railway station. Such device gives more safety awareness to public where this is able to reduce accidents.